Effectiveness of Legal Responsibility and Evaluation in Breach of Contract Cases - Kevin Putra Subagijo; Gunawan Djajaputra (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2025)
This study discusses the effectiveness of the application of legal responsibility to parties who commit default in judicial practice and out-of-court settlement. Default is a form of violation of the contents of the agreement that has been agreed upon by the parties, which can be in the form of not carrying out the performance at all, carrying out the performance not on time, or carrying out the performance not as it should be. In the Indonesian civil law system, provisions regarding default have been clearly regulated in the Indonesian Civil Code, especially in Articles 1234 to 1243 of the Indonesian Civil Code. This study uses a qualitative research method with a descriptive approach, which aims to describe and analyze the extent to which the application of legal responsibility to the perpetrator of default can provide effective legal protection for the injured party, both through the judicial process and alternative dispute resolution. The results of the study indicate that the success of enforcing legal responsibility depends on several factors, including the strength of the evidence, the bargaining position of the parties, and the active role of law enforcement officers and mediation or arbitration institutions. Thus, choosing the right dispute resolution path is key to ensuring justice and legal protection for parties who are harmed due to default.